2017
DOI: 10.1016/j.jneb.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Cooking Matters for Adults Improves Food Resource Management Skills and Self-confidence Among Low-Income Participants

Abstract: This study demonstrated a positive impact of including FRM skills and confidence building in a nutrition education program, the effects of which could be seen for 6 months after participation in the program. Equipping low-income families with FRM skills allowed them to access healthier foods even during times of hardship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 22 publications
4
68
1
Order By: Relevance
“…This individual level approach results in participants who are more confident in their ability to prepare healthy meals. While confidence in food preparation did not translate into significant changes in behaviors, the trend was positive and similar to findings from other evaluations of Cooking Matters and FFESMM [ 42 , 43 , 45 ]. Further, while the education component of this program was only six to nine-weeks and the farmers market was only five weeks, the program that was built on a foundation that the community has sufficiently invested for many years.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This individual level approach results in participants who are more confident in their ability to prepare healthy meals. While confidence in food preparation did not translate into significant changes in behaviors, the trend was positive and similar to findings from other evaluations of Cooking Matters and FFESMM [ 42 , 43 , 45 ]. Further, while the education component of this program was only six to nine-weeks and the farmers market was only five weeks, the program that was built on a foundation that the community has sufficiently invested for many years.…”
Section: Discussionsupporting
confidence: 86%
“…FFCESMH includes a nutrition and physical activity education component, a mobile farmers market, and technical assistance and resources to area faith-based organizations to address the organizational barrier to healthy eating and physical activity. FFCESMH education components combine the practice proven program, Faithful Families Eating Smart and Moving More (FFESMM), with an evidence based program, Cooking Matters (CM) [ 37 , 38 , 42 , 43 , 44 , 45 ]. FFESMM is comprised of nine nutrition and physical activity lessons that are designed to be facilitated by lay leaders from within faith organizations [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These scales have expanded the number and types of skills considered important for home cooking and have shown that both cooking and food skills are critical for shaping dietary intake [23]. Other measures of cooking confidence and attitudes as well as how people perceive what it means to cook (related to the role of convenience foods vs. scratch ingredients and whether heat is required for cooking) have also been shown to be important predictors of cooking behavior [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…This method of statistical analysis is often used by researchers in various fields, for example, in the field of management, marketing, and business [68][69][70][71][72][73]. The method is also used in research projects focused on the field of education [74][75][76][77]. In cases of the questions in which the respondents could choose more than one answer, the responses were evaluated separately.…”
Section: Methodsmentioning
confidence: 99%